Blood acid-base status, some blood gases and electrolytes levels in premature calves - Mahmut Ok; Fatih M. Birdane (Eurasian Journal of Veterinary Sciences)
In this study, acid-base status, the levels of both some blood gases and electrolytes of venous blood were determined in premature and healthy calves. Twenty premature calves and 10 newborn healthy calves were used as a material. The premature calves have 259 to 265 gestation days and 29 to 43 kg body weight, general weakness, soft claw, inability to stand, weak or no sucking reflex, respiratory distress and short silky haircoat. Five out of twenty premature calves died. Venous blood pH, pCO2, pO2</su>, O2SAT ve BE levels were significantly different in the premature calves (p<0.01) compare to the newborn calves.